Variansi Anggaran dan Realisasi Anggaran Belanja Studi Kasus Pemerintah Daerah Provinsi DKI Jakarta - Haryo Kuncoro (Universitas Airlangga, 2008)
The variance of spending is a common figure in any public sectors or even private sectors. In one hand, budget is a statement of performance estimation to be achieved in term of money. On the other hand, the budget realization is an actual achievement report. They could be different from each other because of the pragmatic changes in many factors.Consequently, the difference of those magnitutes indicates asymmetric information. This paper aims at analyzing the variance of expenditure in the case of Jakarta province over the period of 2004-07. Based on the statistical analysis, we conclude that the comparative theory did not hold. As the richest country in Indonesia, Jakarta tended to set spending budget (direct and indirect expenditures) differently across semester. When we investigate across both period and expenditure items, Jakarta did tend to set spending overestimate budget. In short, there were significant budgetary slacks. Those findings above could be associated with the classical problem in coordination of functions, programs, and activities